Poultry health services in Ethiopia: Availability of diagnostic, clinical and vaccination services - Asfaw, Yohannes T.; Ameni, G.; Medhin, G.; Gumi, B.; Wieland, Barbara (Elsevier, 2021)
The fast growth of poultry farming in Ethiopia in recent years has created the need for more and better poultry health services. However, nationwide data showing the coverage and weaknesses of poultry health services in the country are scanty and it has been difficult to design appropriate interventions. Hence, availability of diagnostic, vaccination and clinical services for poultry in Ethiopia were assessed. Focus group discussions and household questionnaire survey were conducted with poultry keepers in 10 districts across four regions and one city administration. Lack of poultry health experts, clinical services, drugs, vaccination, and lack of knowledge and skills were identified as top five key findings which are too low to support substantial growth of the poultry sector in Ethiopia. In total, 31.6% of respondents reported availability of poultry diagnosis service with significant difference among districts. Having flock size of 11-20 chickens had higher probabilities of accessing better diagnosis service (adj OR= 2.77; 95% CI: 1.12-3.64). Access to diagnosis was directly linked with availability of veterinary clinics in their localities (adj odds ratio= 2.65; 95% CI: 1.16-6.63). Moreover, low access to treatment services (22.98%) was reported and traditional remedies with priority index of 0.68 were reported to be most commonly used. Chicken flocks with history of disease occurrence were more likely to have decision to go for modern treatment services (adj OR= 4.26; 95% CI: 2.28-7.95) as compared to those flocks without history of disease occurrence. Only 35.7% of chicken keepers had their flocks vaccinated, and this was irregularly and randomly given, mainly against Newcastle disease. And only 52.9% of them were vaccinated by trained animal health experts. Chicken flocks with availability of veterinary clinics within 5km were more likely (adj OR= 1.62; 95% CI: 1.03-2.54) to have access to vaccination services as compared to those without close-by clinics. Only 53.0% of the chicken flocks had availability of clinics and chicken flocks in Tigray (adj OR= 2.15; 95% CI: 1.03- 4.52) and Oromia (adj OR= 5.74; 95%CI: 2.51-13.10,) had better availability of clinics. Similarly, chicken flocks found in Bako district were less likely (adj OR= 0.41; 95% CI: 0.18-0.92). The low availability of diagnostic, vaccination and clinical services show that poultry health services in Ethiopia has not received Government attention despite it is top national agenda. Hence, the Government and any stakeholders in the country’s poultry sub-sector must give due attention to strategically solve the reported challenges. The existing low poultry health services need to be solved through public-private partnership, producing adequate poultry health experts at different levels (short-term training, BSc, postgraduate graduate diploma, MSc and PhD) and availing vaccines, diagnostics and therapeutics in the local markets.